PERAN LINGKUNGAN DAN PERGAULAN TERHADAP PRESTASI SISWA SEKOLAH SMA NEGERI 1 BATAM - Wasiman Wasiman; Asron Saputra; Poppy Okta Fiana Putri; Mauli Siagian; Nelly Chandrawati Manalu (PUAN INDONESIA, 2026)
The community service program held at SMA 1 Kota Batam, with the theme "The Role of the School Environment and Social Networks in Student Achievement," is quite an interesting topic in the era of technology and Generation Z. The objectives of this community service program are: 1) to provide education and understanding about the importance of student awareness of the school environment, and 2) to provide students with an understanding of the importance of socializing with friends at school and in the community. A comfortable school environment is crucial, considering that the influence of the school environment, such as the physical environment, including the school building, adequate facilities, and infrastructure, significantly impacts student academic and non-academic achievement. The implementation of appropriate learning methods for Generation Z is also necessary to prevent boredom and fatigue in the classroom. Good school social networks can increase student motivation and achievement. Student social groups can shape students' character in learning. This is important because character is formed through group and collaborative learning activities, which students engage in to improve achievement. Furthermore, the role of teachers in shaping students' character, leading to commitment and continuous improvement in school and community achievement, is also crucial.